Manganese Neurotoxicity in Oreochromis niloticus - Herrera, Annabelle; Catap, Elena (Science Diliman: A Journal of Pure and Applied Sciences; Vol 4 No 1 (1992), 2007)
Manganese is not an acutely hazardous environmental contaminant at low levels, but increased dose produces serious degenerative disorders in Oreochromis niloticus . Sublethal exposure of fry to 2000 mg/L manganese chloride for eight days displays evidences of poisoning, and hard hit is the brain. Light microscopy shows appearance of gaps between brain layers and cell destruction. Electron microscopy shows damage to subcellular structures.